Study on the relationship between body mass index and blood pressure indices in children aged 7–17 during COVID-19 - Mao, SuJie; Qian, GuoPing; Xiao, KaiWen; Xu, Hong; Zhou, Hao; Guo, XiuJin (Frontiers in Public Health, 2024)
(1) Background: To explore the relationship between body mass index (BMI), age, sex, and blood pressure (SBP, DBP) in children during COVID-19, providing reference for the prevention and screening of hypertension in children; (2) Methods: This study adopted a large-scale cross-sectional design to investigate the association between BMI and blood pressure in 7-17-year-old students in City N, China, during COVID-19. Thirty-six primary and secondary schools in City N were sampled using a stratified cluster sampling method. A total of 11,433 students aged 7-17 years in City N, China, were selected for blood pressure (Diastolic blood pressure, DBP, Systolic blood pressure, SBP), height, and weight, Resting heart rate (RHR), chest circumference, measurements, and the study was written using the STROBE checklist.(3) Results: The study included 11287 primary and secondary school students, comprising 5649 boys and 5638 girls. It was found that with increasing age, BMI and blood pressure of boys and girls generally increased. There were significant differences in blood pressure levels between boys and girls in different age groups. In regression models, LC, Age, BMI, and chest circumference show significant positive linear relationships with SBP and DBP in adolescents, while RHR exhibits a negative linear relationship with SBP. These factors were individually incorporated into a stratified regression model, significantly enhancing the model's explanatory power. The robustness and predictive accuracy of the model were further examined through K-fold cross-validation and independent sample validation methods. The validation results indicate that the model has a high accuracy and explanatory power in predicting blood pressure in children of different weight levels, especially among obese children, where the prediction accuracy is highest. (4) Conclusions: During COVID-19, age, sex, and BMI significantly influence blood pressure in children aged 7-17 years, and predictive models for SBP and DBP were established. This model helps predict blood pressure in children and reduce the risk of cardiovascular diseases. Confirmation of factors such as sex, age, and BMI provide a basis for personalized health plans for children, especially during large-scale infectious diseases, providing guidance for addressing health challenges and promoting the health and well-being of children.